The Effect of Work-Life Balance on Organizational Citizenship Behavior (OCB) with Organizational Commitment as A Mediation Variable: A Study at PT. Semen Padang: JEL Classification: H83, O33, O38, M15 - Khairani Alya Niktarisya; Hendrik Heri Sandi (Journal of Management and Administration Provision, 2026)
Organizations are required to effectively manage human resources to improve performance and sustainability. One behavior that supports organizational effectiveness is Organizational Citizenship Behavior (OCB). This study aims to analyze the effect of Work-Life Balance on Organizational Citizenship Behavior with Organizational Commitment as a mediating variable among employees of PT Semen Padang. This research uses a quantitative approach with a causal associative design. Data were collected through questionnaires distributed to 127 employees of PT Semen Padang. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results show that Work-Life Balance has a positive and significant effect on Organizational Citizenship Behavior. Work-Life Balance also positively influences Organizational Commitment, and Organizational Commitment significantly affects Organizational Citizenship Behavior. Furthermore, Organizational Commitment is proven to mediate the relationship between Work-Life Balance and Organizational Citizenship Behavior. These findings indicate that better work-life balance increases employees' organizational commitment and encourages voluntary work behaviors that support organizational effectiveness.